2002
DOI: 10.1038/ng873
|View full text |Cite
|
Sign up to set email alerts
|

Topological and causal structure of the yeast transcriptional regulatory network

Abstract: Interpretation of high-throughput biological data requires a knowledge of the design principles underlying the networks that sustain cellular functions. Of particular importance is the genetic network, a set of genes that interact through directed transcriptional regulation. Genes that exert a regulatory role encode dedicated transcription factors (hereafter referred to as regulating proteins) that can bind to specific DNA control regions of regulated genes to activate or inhibit their transcription. Regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
458
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(493 citation statements)
references
References 20 publications
29
458
1
5
Order By: Relevance
“…Figure 1a shows that the gene network has a significant (RAND) broad out-degree distribution, as previously has been observed also in protein and metabolic networks [1]. The distribution does not follow a power-law, as many previously published biological networks do (for example [23]). However, there is no theoretical justification why all networks should have this property, and there are also many examples of when this is not the case (for example [24] …”
Section: Degree Distribution and Categorization Of Out-hubssupporting
confidence: 74%
“…Figure 1a shows that the gene network has a significant (RAND) broad out-degree distribution, as previously has been observed also in protein and metabolic networks [1]. The distribution does not follow a power-law, as many previously published biological networks do (for example [23]). However, there is no theoretical justification why all networks should have this property, and there are also many examples of when this is not the case (for example [24] …”
Section: Degree Distribution and Categorization Of Out-hubssupporting
confidence: 74%
“…A number of topological features are common to the gene regulatory networks in E. coli and yeast 2,3 . A key common feature is that the number of target genes per transcription factor roughly obeys a power law, which is typical of 'scale-free' networks 19 (Fig.…”
Section: All Interactions 1409 906mentioning
confidence: 99%
“…2a), or it may recognize a new binding site upstream of some other target gene(s). Investigation of the known network in both organisms 2,3,7 showed that duplication of transcription factor genes followed by inheritance of interaction has contributed considerably to the growth of the regulatory network: more than two-thirds of E. coli (77%) and yeast (69%) transcription factors have at least one interaction in common with their duplicates (Table 1). This accounts for 128 interactions (10%) in E. coli and 188 interactions (22%) in yeast ( Fig.…”
mentioning
confidence: 99%
“…Network approaches to the analysis of DNA microarray data can reveal interesting properties of genes that are not discernable through standard differential expression analysis (Guelzim et al, 2002;Alon, 2003;Bray, 2003;Ge et al, 2003;Ferrarini et al, 2005). Gene expression is regulated by individual transcription factors, or combinations of such factors, that bind to DNA sequences to promote or inhibit expression of target genes.…”
Section: Introductionmentioning
confidence: 99%
“…In either case, connected genes are often elements of the same biological pathway (Genter et al, 2003;Zhang et al, 2004;Wolfe et al, 2005;Ulitsky and Shamir, 2007), and such genes may participate in similar biological processes (but see Allocco et al, 2004 andYeung et al, 2004a). An interesting property of transcription networks, indeed most biological networks, is a "scale-free" topology, where few hub genes are highly connected to many other genes, with numerous weakly-connected genes located peripherally to highly-connected hubs (Guelzim et al, 2002;Siegal et al, 2007). The density of transcriptional networks, therefore, is distributed in non-random fashion, with certain compact regions corresponding to large gene groups with similar expression patterns.…”
Section: Introductionmentioning
confidence: 99%